SLC6A14 and SLC38A5 Drive the Glutaminolysis and Serine-Glycine-One-Carbon Pathways in Cancer - Tyler Sniegowski; Ksenija Korac; Yangzom D. Bhutia; Vadivel Ganapathy (MDPI AG, 2021)
The glutaminolysis and serine-glycine-one-carbon pathways represent metabolic reactions that are reprogramed and upregulated in cancer; these pathways are involved in supporting the growth and proliferation of cancer cells. Glutaminolysis participates in the production of lactate, an oncometabolite, and also in anabolic reactions leading to the synthesis of fatty acids and cholesterol. The serine-glycine-one-carbon pathway is involved in the synthesis of purines and pyrimidines and the control of the epigenetic signature (DNA methylation, histone methylation) in cancer cells. Methionine is obligatory for most of the methyl-transfer reactions in the form of S-adenosylmethionine; here, too, the serine-glycine-one-carbon pathway is necessary for the resynthesis of methionine following the methyl-transfer reaction. Glutamine, serine, glycine, and methionine are obligatory to fuel these metabolic pathways. The first three amino acids can be synthesized endogenously to some extent, but the need for these amino acids in cancer cells is so high that they also have to be acquired from extracellular sources. Methionine is an essential amino acid, thus making it necessary for cancer cells to acquire this amino acid solely from the extracellular milieu. Cancer cells upregulate specific amino acid transporters to meet this increased demand for these four amino acids. SLC6A14 and SLC38A5 are the two transporters that are upregulated in a variety of cancers to mediate the influx of glutamine, serine, glycine, and methionine into cancer cells. SLC6A14 is a Na+/Cl− -coupled transporter for multiple amino acids, including these four amino acids. In contrast, SLC38A5 is a Na+-coupled transporter with rather restricted specificity towards glutamine, serine, glycine, and methionine. Both transporters exhibit unique functional features that are ideal for the rapid proliferation of cancer cells. As such, these two amino acid transporters play a critical role in promoting the survival and growth of cancer cells and hence represent novel, hitherto largely unexplored, targets for cancer therapy.